A Study of the Impact of Mergers and Acquisitions on Shareholder Wealth of Acquiring Firms in the Short Run: the UK Evidence. - Sun, Yingrong (2015)
This paper investigates the impact of M&A on shareholder wealth of acquiring firms in the short run. Testing on the sample of 909 M&A deals made by UK public acquiring firms between 1997 and 2006, the results reveals that on average, acquiring firms earn significant and positive abnormal returns in both two event windows (-1, +1) and (-2, +2). This proves that shareholders of acquiring firms achieve a significant gain in wealth around the announcement day of M&A. In addition, the wealth effects of six bid and firm characteristics are examined. The evidence shows that around the announcement day of M&A, acquiring firms which have small size, or purchase private targets, or make takeovers with larger relative size can achieve a significantly higher abnormal returns. In addition, cash payment positively influences acquirers’ abnormal returns in the event window (-2, +2). However, such influence is insignificant. Tobin’s q has a significant and negative effect on acquirers’ abnormal returns in the event window (-2, +2). Finally, the impact of relatedness of acquisition is insignificant, but the magnitude of the impact is inconclusive.